2018
DOI: 10.1098/rsfs.2018.0043
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on iridescent neck and breast feathers of the peacock, Pavo cristatus

Abstract: One contribution of 11 to a theme issue 'Living light: optics, ecology and design principles of natural photonic structures'.The blue neck and breast feathers of the peacock are structurally coloured due to an intricate photonic crystal structure in the barbules consisting of a two-dimensionally ordered rectangular lattice of melanosomes (melanin rodlets) and air channels embedded in a keratin matrix. We here investigate the feather coloration by performing microspectrophotometry, imaging scatterometry and ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Here, melanin rodlets (called melanosomes), arranged in a square array, sit in a keratin matrix (interlaced with air gaps). 16,17,[170][171][172] The colours of all blue, green, yellow and orange neck and breast feathers are caused by identical optical effects in the observed 2D photonic crystals. The difference in reected hue simply arises from different periodicities, typically 150 nm for blue feathers and closer to 190 nm for the yellow and green feathers.…”
Section: Papermentioning
confidence: 87%
See 1 more Smart Citation
“…Here, melanin rodlets (called melanosomes), arranged in a square array, sit in a keratin matrix (interlaced with air gaps). 16,17,[170][171][172] The colours of all blue, green, yellow and orange neck and breast feathers are caused by identical optical effects in the observed 2D photonic crystals. The difference in reected hue simply arises from different periodicities, typically 150 nm for blue feathers and closer to 190 nm for the yellow and green feathers.…”
Section: Papermentioning
confidence: 87%
“…16,17,170 More recently, it was shown that simple effective-medium multilayer modelling is suited to modelling these feather colour appearances. 171,172 To analyse the extent of order or disorder in these systems, a Delaunay triangulation algorithm 173 was applied to TEM images of the cross-sections of these structures and the avian dermal structures studied by Prum et al (Fig. 13 and 14), using the method described in ref.…”
Section: Papermentioning
confidence: 99%
“…Effective-medium theory for two-phase nanostructures predicts weighting factors w TE ¼ 2 and w TM ¼ À2 for TE (Transverse Electric)-and TM (Transverse Magnetic)polarised light, respectively. [41][42][43] However, in our previous study on the multilayered blue neck and breast feathers of the peacock, we compared reectance and absorbance spectra modelled with the effective-medium multilayer approach with spectra obtained with the nite-difference time-domain (FDTD) method 31 and found a close correlation when the effective-medium multilayer calculations were performed with slightly modied weighting factors: w TE ¼ 2.5 and w TM ¼ À1.5. We therefore used these adjusted weighting factors in the present study.…”
Section: Effective-medium Multilayer Modellingmentioning
confidence: 99%
“…The measured spectra could be well explained with an effective-medium multilayer model. 31 Extending this approach, here we present a detailed set of reectance spectra of the tail feathers with a comprehensive analysis of the feathers' rich colouration pattern, using recently determined refractive index values of bird keratin and melanin. 16,32 We include all six colour regions that were characterized by Durrer 1,4,5 and highlight the key optical parameters that determine the reectance band shape.…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic brightness is derived from their specific microstructure and the existence of melanosomes, which provide the high refractive index and broadband light absorption. [26][27][28][29] To mimic this phenomenon, various dark elements have been applied to enhance the saturation of the structural colors. Among these elements, GO has significant features of high refractive index, good photothermal effect, relatively large specific surface area, and abundant functional groups on the surface.…”
Section: Progress and Potentialmentioning
confidence: 99%